Interfaces field schools and social movements in Brazil - Ramofly Bicalho Santos (Universidade Federal do Norte do Tocantins, 2016)
This article has as main objective to present reflections on the critical production of knowledge, linked to the principles of the field of education and values against hegemonic defended by social movements. We carried out a succinct approach, indicating the main problems facing the closure of schools in the field. Developed a bibliographical and documentary research, using sources of research, laws, ordinances, decrees and theoretical frameworks produced on this theme in Brazil. We conclude that the collective production of knowledge, in partnership with students, educators, communities and social movements struggling for land, can dialogue with stories, memories, identities, desires, values and recognition, strengthening the debates around the field education, close relationship with public universities, schools, municipal and state education. We note that this joint is one of the main challenges to be faced by the subjects, individual and collective. The school, in this sense, can provide reflections that educates and helps to point out ways of a more human reality for many rural populations.